Ex-situ biological treatment of industrial saline seafood wastewater by salt-tolerant mixed cultures and phytotoxicity evaluation - Tsipa, Argyro; Papalli, Maria; Christou, Andreas; Pissaridou, Panayiota; Vasquez Christodoulou, Marlen (My University, 2023)
In the framework of circular economy, this study assessed the ex-situ biodegradation and desalination of saline non-sterilized seafood wastewater (SFW) by new salt-tolerant mixed bacterial cultures, followed by its phytotoxicity evaluation. These cultures were characterized through 16S amplicon sequencing, an advanced tool to process the biodiversity of samples empowering applicability to advanced bioprocessing of SFW. The mixed cultures had high relative abundance of Pseudomonas and Aeromonas, and abundance of Acinetobacter, Myroides and Chryseobacterium. The biodegradation potential, growth kinetics and specific growth rate of the mixed cultures were determined using varying concentrations of SFW (20% and 80% v/v). The process was completed in just 24 h resulting in no odour and colour. The mixed cultures were also combined. Effective Chemical Oxygen Demand (COD) removal (36.2-89.1%) was achieved by the mixed cultures and their combinations. The mixed cultures resulted in significant salt content reduction (77.5-83.3%). The considerably lower levels of COD (<900 mg/L) and salt content achieved, in most cases, is a step towards in-situ SFW treatment before entrance to the sewage system. Among all, mixed Pseudomonas sp. dominant cultures were the most promising for further in-situ bioprocessing studies. In addition, the biotreated SFW supernatant, which was not overly-diluted using freshwater, could potentially be reused in agriculture, as the germination index was higher than 50% upon seed and root growth of tomato and lettuce. It contained approximately 0.03% total nitrogen and 0.01% phosphate which may irrigate to plants providing additional nutrients.
Keywords: Biodegradation; Bacterial community composition; Salt-reduction; Germination index; Wastewater reuse; 16S amplicon sequencing